Can elderly patients regain their preoperative functional level after distal radius fracture type A? Results from a fracture register study using PROM - Von Matthey, F.; Rammensee, J.; Müller, M.; Biberthaler, P.; Abel, H. (Frontiers in Surgery, 2023)
Introduction Although distal radius fractures (DRFs) are the most common fractures of the human body, there are still ongoing debates concerning the treatment for type A fractures, especially in elderly patients. In spite of good clinical outcomes, it remains unclear whether elderly patients, especially, could regain the preoperative functional level of the wrist. Therefore, we have quantified wrist function within a retrospective study design using patient-reported outcome measures (PROM) and we have analyzed the influence of age between control and patient collective and young vs. old, respectively. Patients and methods The retrospective study included all patients with a surgically treated DRF type A and a control group of healthy patients, age and gender matched. The function of the wrist was examined by using a self-assessment questionnaire called the Munich Wrist Questionnaire (MWQ) according to the patient-related outcome measurements PROM. Results We could enroll 110 patients and controls, and the average follow-up was 66 months. Subgroup matching induced similar age group distribution: in both groups, 7 individuals <30 years, 67 between 31 and 64 years, 29 between 65 and 79 years, and 7 individuals >80 years, were enrolled, respectively. In the fracture group, women were significantly older than men (59 ± 15 vs. 47 ± 17 (M ± SD). There was no significant difference between the control and the patient groups (96 ± 6 vs. 95 ± 7). The function was significantly different between controls and patients <30 years (100 ± 1 vs. 98 ± 2). In the control group, there was a functional difference in the age group <30 compared with 65–79 and >80 and in the age group 30–64 compared with 65–79 and >80. In the control group, the function was found to be significantly decreasing with advancing age, whereas in the patient group, this influence was absent. A correlation analysis showed a worse function with increasing age in the control group and therefore a negative correlation. In the fracture group, a similar result could not be obtained. Discussion Age has a relevant influence on wrist function. Although the wrist function decreases significantly with aging, in the patient group, this influence is absent, and the functional results after surgery are excellent. Even elderly patients can regain their preoperative functional level.